2022
DOI: 10.1111/apt.16892
|View full text |Cite
|
Sign up to set email alerts
|

Toward transmural healing: Sonographic healing is associated with improved long‐term outcomes in patients with Crohn’s disease

Abstract: Background and Aims Transmural healing has emerged as a treatment target in Crohn’s disease (CD). We investigated whether transmural healing assessed with intestinal ultrasound (IUS) is associated with improved clinical outcomes in patients with CD in clinical remission. Methods Patients with CD in clinical remission at baseline (HBI <4) having IUS between August 2017 and June 2020 with at least 6‐months’ follow‐up were retrospectively studied. Time to medication escalation, corticosteroid use and CD‐related h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…There is increasing evidence that such indices relate poorly to the inflammatory activity of the disease. For example, in patients with CD, inflammatory activity defined by sonographic criteria was present in 61% of patients in remission according to the Harvey-Bradshaw Index [35]. The disparity between disease activity scores on the one hand and FCP, SMI and response to therapy on the other is further evidence that clinical disease activity scores provide few predictive clues to the inflammatory activity and the effects of the disease on body composition.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that such indices relate poorly to the inflammatory activity of the disease. For example, in patients with CD, inflammatory activity defined by sonographic criteria was present in 61% of patients in remission according to the Harvey-Bradshaw Index [35]. The disparity between disease activity scores on the one hand and FCP, SMI and response to therapy on the other is further evidence that clinical disease activity scores provide few predictive clues to the inflammatory activity and the effects of the disease on body composition.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a recent multicenter Italian study of adult patients with CD treated with various biologic therapies demonstrated higher rates of TH (defined as normalization of all IUS parameters) with improvement in IUS in 53% at 3 mo and 64% by 1 year with a number needed to treat of 3.6 patients in order to achieve TH. Compared to MH alone, TH is associated with improved outcomes and a decreased risk of long-term disease progression[ 29 , 30 , 35 , 36 ].…”
Section: Monitoring Disease Activity and Treatment Responsementioning
confidence: 99%
“…Furthermore, in a subanalysis of patients with TH, there was no significant difference for steroid‐free clinical remission between patients withdrawing anti‐TNFs and patients continuing the medication, but patients suspending the anti‐TNF agent required more frequent hospitalization and were at a high risk of losing their TH status (15). A recent retrospective study conducted by Vaughan et al (31) demonstrated during median follow-up of 19 (interquartile range 13–27) months, sonographic healing was significantly associated with a reduced risk of medication escalation, corticosteroid use, hospitalization, and surgery. On multivariable analysis, sonographic healing was significantly associated with an increased odds of medication escalation-free survival and corticosteroid-free survival, but not with hospitalization or surgery.…”
Section: Ultrasonography Th Modifies the Course Of CDmentioning
confidence: 99%